Effects of long-term supplementation of probiotics on cognitive function and emotion in temporal lobe epilepsy - Wang, Xue; Ma, Rui; Liu, Xinyi; Zhang, Yongbo (Frontiers in Neurology, 2022)
Cognitive impairment and neuropsychiatric disorders are very common in patients with temporal lobe epilepsy (TLE). These comorbidities complicate the treatment of epilepsy and seriously affect the quality of life. So far, there is still no effective intervention to prevent the development of epilepsy-associated comorbidities. Gut dysbiosis has been recognized to be involved in the pathology of epilepsy development. Modulating gut microbiota by probiotics has shown an antiseizure effect on humans and animals with epilepsy. Whether this treatment strategy has a positive effect on epilepsy-associated comorbidities remains unclear. Therefore, this study aimed to objectively assess the effect of probiotics on cognitive function and neuropsychiatric performance of patients with TLE. Participants enrolled in an epilepsy clinic were randomly assigned to the probiotic and placebo groups. These two groups were treated with probiotics or placebo for 12 weeks, and then the cognitive function and psychological performance of participants were assessed. We enrolled 76 participants in this study, and 70 subjects were finally included in the study (35 in the probiotics group and 35 in the placebo group). Our results showed significant seizure reduction in patients with TLE treated with probiotics. Meanwhile, participants treated with probiotics showed significant improvement in intelligence (processing speed index [PSI], working memory index, and full-scale IQ) and memory (auditory memory index, visual memory index, immediate memory index, and delayed memory index [DMI]), and improvements in PSI and DMI were independent of seizure reduction. In addition, probiotics decreased the Hamilton Anxiety Rating and Depression Scale scores and increased the 89-item Quality of Life in Epilepsy Inventory score in patients with TLE. In conclusion, probiotics have a positive impact on cognitive function, and improve anxiety, depression, and quality of life in patients with TLE.